CONSTRUCTING MILLENIAL STUDENT DISCIPLINE CHARACTER THROUGH AWARDING REWARD-STICKER - Abd. Muqit; Khairul Auliyah; Akhmad Nurul Kawakip; Muh. Hambali; Moh. Nawafil (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2022)
This research aims to analyze data related to the implementation of giving sticker rewards in shaping students' disciplinary character. The research approach uses a qualitative type of case study. Data collection using observation techniques, interviews, and documentation. Data analysis techniques in this study consisted of data condensation, data presentation, then the stages of conclusion. The results of this study are 1) giving rewards in shaping the character of student discipline through the distribution of stickers which are very important in motivating students to take positive actions; 2) The steps for giving reward stickers start with preparing learning materials, conveying material to students, observing students' attitudes, the lastly giving reward stickers to students who have done good performance; 3) Factors supporting the success of this program are good motivation from teachers, self-awareness in students, libraries, places of worship, and proportionate classes. While the inhibiting factors are the playing environment and colleagues. Abstrak Penelitian ini bertujuan untuk menganalisis data terkait pelaksanaan pemberian reward sticker dalam membentuk karakter disiplin siswa. Pendekatan penelitian menggunakan kualitatif, jenis studi kasus. Pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Teknik analisis data dalam penelitian ini terdiri dari kondensasi data, penyajian data, kemudian tahapan penarikan kesimpulan. Hasil penelitian ini adalah 1) pemberian reward dalam membentuk karakter kedisiplinan siswa melalui pendistribusian stiker sangat penting dalam memotivasi siswa untuk melakukan tindakan positif; 2) Langkah-langkah pemberian reward-sticker diawali dengan menyiapkan materi pembelajaran, menyampaikan materi kepada siswa, mengamati sikap siswa, terakhir memberikan reward-stiker kepada siswa yang berprestasi baik; 3) Faktor pendukung keberhasilan program ini adalah motivasi yang baik dari guru, kesadaran diri pada siswa, perpustakaan, tempat ibadah, dan kelas yang proporsional. Sedangkan faktor penghambatnya adalah lingkungan bermain dan teman sejawat.